2014
DOI: 10.1371/journal.pone.0109610
|View full text |Cite
|
Sign up to set email alerts
|

Operator Dependent Choice of Prostate Cancer Biopsy Has Limited Impact on a Gene Signature Analysis for the Highly Expressed Genes IGFBP3 and F3 in Prostate Cancer Epithelial Cells

Abstract: BackgroundPredicting the prognosis of prostate cancer disease through gene expression analysis is receiving increasing interest. In many cases, such analyses are based on formalin-fixed, paraffin embedded (FFPE) core needle biopsy material on which Gleason grading for diagnosis has been conducted. Since each patient typically has multiple biopsy samples, and since Gleason grading is an operator dependent procedure known to be difficult, the impact of the operator's choice of biopsy was evaluated.MethodsMultipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…86 Conversely, Long et al 86 have demonstrated consistent gene expression across multiple biopsy cores in a single patient, supporting previous work revealing limited variation in gene expression levels of highly expressed genes across multiple biopsy cores, including both malignant and benign stromal tissue. 88 As others have noted, such consistent gene expression, despite tissue and tumor heterogeneity, supports the notion that one can be confident in the overall prostate biology based on analysis of a limited sample. 89 …”
Section: Molecular Testing In Active Surveillancesupporting
confidence: 68%
“…86 Conversely, Long et al 86 have demonstrated consistent gene expression across multiple biopsy cores in a single patient, supporting previous work revealing limited variation in gene expression levels of highly expressed genes across multiple biopsy cores, including both malignant and benign stromal tissue. 88 As others have noted, such consistent gene expression, despite tissue and tumor heterogeneity, supports the notion that one can be confident in the overall prostate biology based on analysis of a limited sample. 89 …”
Section: Molecular Testing In Active Surveillancesupporting
confidence: 68%
“…3 In addition, Long et al demonstrated that there is a strong correlation of gene expression across separate biopsy cores from the same patient, 40 a finding that was similar to that of a study by Peng et al that suggested that there was limited, operator choice-dependent variation in gene signature analysis of highly expressed genes across multiple biopsy samples, primary versus secondary Gleason patterns, and primary versus benign tissue. 41 This consistency of gene expression, regardless of interbiopsy or intrabiopsy tumor heterogeneity, reinforces the current understanding that it is possible to be confident in the biology of the entire prostate based on analysis of gene expression in a biopsy sample.…”
Section: Molecular Risk Profiling As a Substitute For Early Confirmatsupporting
confidence: 59%
“…The sample preparation process is described by Peng et al [ 9 ]. The results reported here were mainly obtained at the same time as the results reported by Peng et al [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Even though the extracted RNA from FFPE samples may be of relatively low quality, multiple recent studies have shown promising results when utilizing degraded RNA extracted from archival FFPE samples for quantifying gene expression levels by optimized RT-qPCR methods [ 6 8 ]. One example is the Prostatype RT-qPCR kit, which is developed and optimized for measuring the gene expression levels of a gene signature of IGFBP3, F3 and VGLL3 particularly in FFPE samples [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation